(untitled) (Scientific journal of the Fergana State University, 2024)
Avizenna in the first place, well-known as a great healer, moreover he was still popular among scientists as a philosopher. He urged people to science, culture and education, he still taught the people to consciously solve different types of questions in terms of fairness and justice. This article describes Avizennaʻs advanced ideas not only expressed in his works devoted to the development of natural sciences, but also found in his poems and short stories.